SOCIALIZATION OF THE GRANTING OF INTEGRATION RIGHTS TO NON-HEIRS OF RELIGIOUS MODERATION PERSPECTIVE - Muhammad Syakir Al Kautsar; Nurul Mahmudah (MODERATIO: Jurnal Moderasi Beragama, 2021)
The socialization of granting inheritance rights to non-heirs from a moderate perspective is to take place in religion because there are two important factors, namely social environmental factors and family factors. This socialization is greatly influenced by education and the ability of the community to accept opinions. Thus, the supporting and inhibiting factors of the Community Service team's socialization activities were carried out. If young people are active and invite people to participate in religious activities, one of the activities is understanding Islamic law. Then behavior in activities based on sharia, especially Islamic inheritance can be reduced